Health information seeking behaviour among the Kuwaiti population during the COVID-19 pandemic - Aldousari, Elham A; Al-Sejari, Maha (Malaysian Journal of Library and Information Science, 2021)
This study investigates health information seeking behaviour during the COVID-19 pandemic based on a survey of 1,018 residents in Kuwait. An online questionnaire was used to collect the data using convenience sampling method. More than half the respondents reported following news updates on COVID-19 through websites produced by the Kuwaiti Ministry of Health (MOH), local TV channels, and social media networks. They were aware of most of the precautions being prescribed to curb the spread of the virus. Official resources that helped improve the participants’ health information seeking behaviour included receiving text messages from government agencies and watching daily press coverage of news conferences held by the MOH. Health information seeking behaviour for COVID-19 varied among the respondents according to socio-demographic characteristics. Male respondents had sought more health-related information than the females. Respondents aged 18 to 29 years and student groups were more likely than others to follow news updates on COVID-19; were more aware of the relevant precautionary practices; and were more likely to improve their health literacy. The findings of this study provide a clear account of public health information-seeking behaviour in Kuwait during the pandemic.